Teologi Ahmadiyah di Indonesia - Monica, adelia; Nur, Aidia Lailika; Fauzi, Alfin Mahfudz; Sajari, Dimyati (Universitas Islam Negeri Raden Intan Lampung, 2023)
Abstract;Ahmadiyah is one of the many organizations that emerged from existing ideas. Ahmadiyah is an organization founded by Mirza Ghulam Ahmad in India. Currently the spread of the Ahmadiyah organization has been prohibited in Indonesia in accordance with the Decree of the 3 Ministerial Decree and Governor's Regulation Number 12 of 2011 concerning the Prohibition of Ahmadiyah Teachings in West Java Province as well as with the MUI fatwa regarding the misdirection of the Ahmadiyah organization. Therefore, this journal will discuss the background to the emergence of the Ahmadiyah organization, theology and the existence of Ahmadiyah in Indonesia. This research uses a qualitative description approach and collects data using a literature review method. The doctrines that often give rise to misunderstandings spread by the Ahmadiyah movement include those regarding revelation, prophethood, and the Mahdi and the Messiah. This doctrine then gave rise to controversy regarding the Ahmadiyah organization and caused it to receive discrimination in various places.Keywords:Ahmadiyya; Doctrine; Existence. Abstrak;Ahmadiyah merupakan salah satu dari banyaknya organisasi yang muncul dari hasil pemikiran-pemikiran yang ada. Ahmadiyah ialah organisasi yang didirikan oleh Mirza Ghulam Ahmad di India. Saat ini penyebaran organisasi Ahmadiyah telah dilarang di Indonesia sesuai dengan kuputusan SKB 3Menteri dan Peraturan Gubernur Nomor 12 Tahun 2011 tentang Larangan Ajaran Ahmadiyah di Provinsi Jawa Barat serta dengan fatwa MUI mengenai penyesatan organisasi Ahmadiyah. penelitian ini akan membahas mengenai latar belakang munculnya organisasi Ahmadiyah, Teologi dan eksistensi Ahmadiyah di Indonesia. Penelitian ini menggunakan pendekatan deskripsi kulitatif dan dalam pengumpulan data menggunakan metode kajian pustaka. Doktrin yang sering menimbulkan kesalah fahaman yang disebarkan oleh gerakan Ahmadiyah diantaranya ialah mengenai wahyu, kenabian, dan Al Mahdi dan Al-Masih. Doktrin inilah yang kemudian memunculkan kontroversi mengenai organisasi Ahmadiyah serta membuatnya menerima diskriminasi di berbagai tempat.Kata Kunci: Ahmadiyah; Doktrin; Eksistensi.